2005
DOI: 10.1016/j.ijcard.2004.05.010
|View full text |Cite
|
Sign up to set email alerts
|

An affected pedigree member analysis of linkage between the dopamine D2 receptor gene TaqI polymorphism and obesity and hypertension

Abstract: Our data in normoglycaemic Hong Kong Chinese supports that the DD2R gene TaqI polymorphism is a marker associated with the pathogenesis of obesity and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…This is consistent with genetic studies, which have specifically implicated the D2 receptor gene (TAQ-IA polymorphism), as one that is involved in vulnerability to obesity (Fang et al, 2005;Pohjalainen et al, 1998;Bowirrat and Oscar-Berman, 2005). Moreover, the TAQ-IA polymorphism, which appears to result in lower D2 receptor levels in brain (striatum) (Ritchie and Noble, 2003;Pohjalainen et al, 1998; Jonsson et al, 1999) was recently found to be associated with decreased ability to inhibit behaviors that result in negative consequences and with impaired activation of prefrontal regions (Klein et al, 2007).…”
Section: Association Between D2 Receptors and Prefrontal Metabolismsupporting
confidence: 90%
“…This is consistent with genetic studies, which have specifically implicated the D2 receptor gene (TAQ-IA polymorphism), as one that is involved in vulnerability to obesity (Fang et al, 2005;Pohjalainen et al, 1998;Bowirrat and Oscar-Berman, 2005). Moreover, the TAQ-IA polymorphism, which appears to result in lower D2 receptor levels in brain (striatum) (Ritchie and Noble, 2003;Pohjalainen et al, 1998; Jonsson et al, 1999) was recently found to be associated with decreased ability to inhibit behaviors that result in negative consequences and with impaired activation of prefrontal regions (Klein et al, 2007).…”
Section: Association Between D2 Receptors and Prefrontal Metabolismsupporting
confidence: 90%
“…This implies that the ancestral forms of the two sites (A1 and B2) are present at high frequencies in African populations, whereas in rest of the world, as supported by the presently studied populations, the ancestral A1 allele is present at low frequency, pushing the A2 allele to a higher frequency that is similar to that of the B2 allele. A1 has a selective disadvantage because of its clinical association with addictive disorders like alcoholism and hypertension (Blum et al, 1991;Noble, 2003;Fang et al, 2005) and, as such, its frequency has been reduced in many populations of world, including India. As the TaqIA site is in linkage disequilibrium with the TaqIB site in most populations studied, the variation in B2 frequencies is related to the A2 allele.…”
Section: Discussionmentioning
confidence: 99%
“…Several of the GPCRs in the cluster are related to obesity traits in mice when mutated or overexpressed [3336], and others have been proposed as candidate genes for human obesity [3739] (Figure S3A). An additional subset of the GPCR cluster represents GABA receptor subunits (Figure S3B).…”
Section: Discussionmentioning
confidence: 99%